SUSTAINABLE TOURIST REQUALIFICATION OF THE BARDO DISTRICT CONSTANTINE – ALGERIA - Afef Messaoudi; Meriama Bencherif (International Journal of Innovative Technologies in Social Science, 2025)
Tourism, long neglected by urban managers, is now recognized as a key sector for the attractiveness of cities. Today, urban planning can no longer ignore this sector, as cities attract visitors through the tourism opportunities and events they offer. Urban spaces are being designed to highlight activities, exchanges, and meetings, making tourism an important pillar of the city’s development strategy. This research aims to reintegrate the city of Constantine, particularly its historic center, into the development dynamic, focusing on the old town and its surroundings marked by the declining colonial fabric and the endangered Bardo district, considered "sites in need" of development and attractiveness. The challenge is to reintegrate them into a virtuous circle of value creation and regeneration. Located in northeastern Algeria, Constantine had a population of over 80,000 in 2016. One of the oldest cities in North Africa, it plays a major role in Mediterranean history. Its strategic geographical location, at the intersection of major North-South (Skikda-Biskra) and East-West (Sétif-Annaba) axes, enables it to perform significant cultural and industrial functions. Over the years, the city has transformed and expanded due to demographic and economic growth, the explosion of individual mobility, and competition for space. It is now necessary to restore meaning, coherence, and legibility to the territory, sometimes scattered, while addressing the consequences of a city disfigured by the dominance of cars and parking. The peripheral neighborhoods, just like the historic center, can become quality urban spaces and contribute to the city’s attractiveness, as opposed to the undefined peripheral areas. Thus, reclaiming struggling neighborhoods through their requalification can be a powerful lever for enhancing the city of Constantine. This offers residents access to modernity, improving quality of life and social cohesion, fostering a sense of belonging, and becoming a key element of the place’s or community’s identity. Through this research, we seek to shed light on the issue of planning and promotion actions that accompany and reveal the ways of valorizing the city and its image, transforming it from an active city to a festive city, from a city of need to a city of desire. This transformation takes place through reflection on urbanity, culture, heritage, mobility, the reorganization of spaces and urban networks, and the places’ capacity to accommodate. In this perspective, our efforts have focused on the originality of the approach, based on seeking innovation through the requalification of struggling peripheral neighborhoods and their integration into the surrounding urban fabric, through the creation of an urban park and cultural and tourist facilities, while respecting the criteria of sustainable development. The image of the city of Constantine, reconciling its past with its future through sustainable tourism and heritage valorization, requires a more humanistic and coordinated urban policy. This policy favors soft, progressive requalifications, supported by public actions with strong symbolic significance, actively involving residents in the project and engaging a variety of private operators.